Probing lewis acidity and reactivity of Sn- and Ti-beta zeolite using industrially important moieties: a periodic density functional study - Kulkarni, Bhakti S.; Krishnamurty, Sailaja; Pal, Sourav (Journal of Molecular Catalysis A-Chemical, 2010)
The Lewis acidic nature and reactivity of two industrially important catalysts, viz.. Sn and Ti substituted beta zeolite (T-BEA) are analyzed using a unique combination of structural parameters, energetics and reactivity descriptors. To achieve this purpose, we adsorb the industrially important moieties (L) namely NH(3), H(2)O, CH(3)OH, CH(3)CN on the active sites of T-BEA. The calculations were performed using a periodic density functional method where the valence electrons are described using a plane wave basis set in conjunction with pseudo-potentials for the core electrons. The analysis of the structural properties of these complexes reveals that TO(4) shows typical characteristic splitting 120 degrees/90 degrees, close to bipyramidal geometry as compared to tetrahedral symmetry observed in the bare T-BEA. This is associated with small variations in the framework bond lengths (>= 0.08 angstrom) and a substantially large variation of bond angles (<= 10 degrees) in all the ligand-zeolite complexes. Further in both cases of Sn and Ti substituted beta zeolite, ligand interacts at optimum inter-atomic bond distance. Our interaction energies show that adsorption of all ligand moieties is stronger at Sn center than that of Ti. In general, the order of stability of the different T-BEA adducts is NH(3) > H(2)O > CH(3)OH > CH(3)CN. The ligand interaction is associated with the corresponding bond elongation and bond reduction of the adsorbed molecules on catalyst active site, which can be taken as measure of red or blue shifted frequencies. Finally, the global descriptors of reactivity justify the fact that soft acid, Sn-BEA, interacts strongly with soft bases following the Pearson's HSAB principle. However, hard acid, Ti-BEA interacts with soft bases to form a stable Lewis adduct. Furthermore, the HOMO-LUMO gap of all Sn-BEA-L adducts is lower than that of Ti-BEA-L adducts indicating to its higher Lewis acidic nature compared to Ti-BEA. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Beta zeolite; Lewis acidity; Ligand-zeolite complex; Periodic-DFT; Reactivity descriptors

Performance of the EOMIP-CCSD(2) method for determining the structure and properties of doublet radicals: a benchmark investigation - Dutta, Achintya Kumar; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2013)
We present a benchmark study on the performance of the EOMIP-CCSD(2) method for computation of structure and properties of doublet radicals. The EOMIP-CCSD(2) method is a second-order approximation to the standard EOMIP-CCSD method. By retaining the black box nature of the standard EOMIP-CCSD method and adding favorable N-5 scaling, the EOMIP-CCSD(2) method can become the method of choice for predicting the structure and spectroscopic properties of large doublet radicals. The EOMIP-CCSD(2) method overcomes the typical problems associated with the standard single reference ab initio treatment of doublet radicals. We compare our results for geometries and harmonic vibrational frequencies with those obtained using the standard EOMIP-CCSD method, as well as unrestricted Hartree-Fock (UHF)- and restricted open-shell Hartree-Fock (ROHF)-based single-reference coupled-cluster and second order many-body perturbation theory (MBPT(2)) methods. The effect of the basis set on the quality of the results has been studied using a hierarchy of Dunning's correlation-consistent aug-cc-pVXZ (X = D, T, Q) basis sets. Numerical results show that the EOMIP-CCSD(2) method, despite its N-5 scaling, gives better agreement with experimental results, compared to the UHF- and ROHF-based MBPT(2), as well as the single-reference coupled-cluster methods.

Perturbative approximations to single and double spin flip equation of motion coupled cluster singles doubles methods - Dutta, Achintya Kumar; Pal, Sourav; Ghosh, Debashree (Journal of Chemical Physics, 2013)
Spin flip equation of motion coupled cluster (EOM-SF-CC) can correctly treat situations involving electronic degeneracies or near degeneracies, e. g., bond breaking, di- and tri-radicals, etc. However, for large systems EOM-SF-CC (even in single and double excitations) is computationally prohibitively expensive. Therefore, earlier approximations to EOM-SF-CC methods such as spin flip configuration interaction singles with perturbative doubles (SF-CIS(D)) have been proposed. In this work, we present a new perturbative approximation to EOM-SF-CC, which has been found to be more accurate than SF-CIS(D). The capabilities, advantages, and timings of the new approach have been demonstrated considering the singlet-triplet gaps in di- and triradicals as well as bond breaking examples. The method is extended to double spin flip EOM-CC and its capabilities have been tested. (C) 2013 AIP Publishing LLC.

Polarizability of few electron quantum dots: extended coupled-cluster response approach - Heidari, Ideh; Vaval, Nayana; Pal, Sourav; Kanhere, Dilip G. (Chemical Physics Letters, 2013)
The dipole polarizability is studied for few electron quantum dots using extended coupled cluster linear response method (ECCLR). The polarizability of pure parabolic quantum dots depends only on the number of electrons and the parabolic confinement strength. We added impurity in a GAUSSIAN form to the external parabolic potential and used ECCLR to calculate polarizability. To examine the effect of external potential, we changed the parabolic confinement to square-well and repeated all calculations. We mainly looked at eigenvalue spectrum and charge density specially when the system shifts towards lower density regions. (C) 2012 Elsevier B. V. All rights reserved.

Partitioned EOMEA-MBPT(2): an efficient N-5 scaling method for calculation of electron affinities - Dutta, Achintya Kumar; Gupta, Jitendra; Pathak, Himadri; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2014)
We present an N-5 scaling modification to the standard EOMEA-CCSD method, based on the matrix partitioning technique and perturbative approximations. The method has lower computational scaling and smaller storage requirements than the standard EOMEA-CCSD method and, therefore, can be used to calculate electron affinities of large molecules and clusters. The performance and capabilities of the new method have been benchmarked with the standard EOMEA-CCSD method, for a test set of 20 small molecules, and the average absolute deviation is only 0.03 eV. The method is further used to investigate electron affinities of DNA and RNA nucleobases, and the results are in excellent agreement with the experimental values.

Photoelectrochemical splitting of water with nanocrystalline Zn1-xMnxO thin films: first-principle DFT computations supporting the systematic experimental endeavor - Sharma, Vidhika; Dixit, Mudit; Satsangi, Vibha R.; Dass, Sahab; Pal, Sourav; Shrivastav, Rohit (International Journal of Hydrogen Energy, 2014)
Photoelectrochemical splitting of water with nanocrystalline Zn1-xMnxO thin films was investigated. ZnO thin films with 1, 3, 5 and 7% at. Mn incorporation were synthesized by sol gel method and characterized by X-Ray Diffraction (XRD) analysis, Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM), X-ray Photoelectron spectroscopy (XPS), High Resolution Transmission Electron Microscopy (HR-TEM) and UV-Vis spectroscopy. Mn incorporation coupled with variation in sintering temperature led to significant microstructural changes, which tentatively influenced the magnitude of optical absorption and charge carrier mobility, thereby impacting the performance of such systems towards photoelectrochemical splitting of water. Electronic structure computations based on first principle density functional theory (DFT) revealed electronic states of Mn being responsible for the marginally recorded red shift in bandgap energy. Photoelectrochemical measurements using thin films of 1% at. Mn:ZnO sintered at 600 degrees C yielded 3 times enhanced photocurrent at zero bias due to improved optical absorption. Plausible explanations for the effect have also been offered. Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Density functional theory; Hydrogen energy; Mn doped ZnO; Optical properties; Photoelectrochemical water splitting

Partial triples excitation to the fock space multi-reference singles and doubles: dipole moment of doublet radicals - Ravichandran, Lalitha; Vaval, Nayana; Pal, Sourav (Proceedings of the International Conference of Computational Methods in Sciences and Engineering 2010 (ICCMSE-2010), 2015)
We present the partial triples effect on the dipole moment of doublet radicals in Lagrangian formulation of Fockspace multi-reference coupled cluster response method(A FSMRCC). This specific scheme uses non-iterative triples, in addition to singles and doubles excitations(A FSMRCCSD(T*)), which accounts for the effects appearing at least at the third order in dipole moment. This method is applied to the ground states of small radicals.
Keywords: Dipole moment; Multi-reference; Triples

Perturbative order analysis of the similarity transformed hamiltonian in fock-space coupled cluster theory: difference energy and electric response properties - Bhattacharya, Debarati; Dutta, Achintya Kumar; Gupta, Jitendra; Pal, Sourav (Molecular Physics, 2015)
A perturbative analysis of the ground-state similarity transformed Hamiltonian and its effect on the various Fock-space coupled cluster (FSCC) sectors is presented through calculation of ionisation potential, electron affinity, excitation energies and response properties. Various truncation schemes of the effective Hamiltonian are presented with explicit form of the defining equations. Based on such a truncation, the approximate methods are labelled as FSCC(n), where n represents the correlation energy of the ionised, electron attached or excited states corrected at least up to nth order within coupled cluster singles and doubles scheme (CCSD). A lower scaling CC2 type of approach (abbreviated as FS-CC2) is compared against the group of FSCC(n) methods for energies. Electric response properties have been compared and contrasted for the two lower scaling methods: FSCC(2) and FS-CC2. The various truncated methods are tested for a number of small molecules. The results obtained from a range of truncated methods are compared against full FSCCSD calculations.
Keywords: electric response properties; Fock space; perturbative order; similarity transformed Hamiltonian